A Spotlight of Co-creation and Inclusiveness of Public Open Spaces - Šuklje Erjavec, Ina; Ruchinskaya, Tatiana (CyberParks – The Interface Between People, Places and Technology: New Approaches and Perspectives, 2019)
This chapter focuses on co-creation as the way to engage different stakeholders with everyday urban environments based on equality, diversity and social cohesion. It presents the relationship of co-creation and inclusiveness of public open spaces together with different aspects of co-creation related to issues of publicness and space. It discusses why and how co-creation must take into consideration the characteristics of the comprehensive spatial development processes. It suggests that co-creation is a wider concept than co-design and is a multistage process that contributes to inclusive public spaces, providing measures for social sustainability of place. This chapter argues that digital tools may help to overcome challenges of co-creation and provide an opinion on the contribution of digital technologies to the co-creation process by engaging people in the design, use and management of public spaces, providing new resources for interaction and users’ empowerment. For that it presents an overview of the possible contribution of digital technologies to support inclusiveness of the co-creation processes that is structured by typologies of digital tools and their possible interlinking with the steps of the co-creation process. To improve the understanding of such possibilities it critically addresses strengths and weaknesses of using digital tools for co-creation and inclusiveness and provides recommendations for their further development.
Keywords: Co-création; Inclusion; Outil numérique

The Art of Co-Creation: a Guidebook for Practitioners - Rill, Bryan R.; Hämäläinen, Matti M. (Palgrave Macmillan, 2018)
This book illustrates how to design and implement co-creation, a powerful form of collective creativity that harnesses the potential of teams and can generate breakthrough insights. Skilled leaders and facilitators can utilize this approach to unleash the creative potential of their organizations. Drawing from years of applied research, the authors bring together insights from the fields of design and organizational development into an evocative and pragmatic "how-to" guidebook. Taking a human-centred rather than process oriented perspective, the book argues that experience design separates true co-creation from other forms of collective efforts and design thinking. Collective moments of creative insight emerge from the space between, an experience of flow and synchronicity from which new ideas spring forth. How to create and hold this space is the secret to the art of co-creation. Collective breakthroughs require stakeholders to undergo a journey from the world of their existing expertise into spaces of new potential. It requires leaders moving from a position of dominating space to holding the space for others, and developing core capacities such as empathy and awareness so that teams can engage each other co-creatively. This book uncovers the secrets of this journey, enabling process designers to develop more effective programs.
Keywords: Co-création; Créativité collective; Méthodes; Réservé UdeM

Guide pratique sur la cocréation - Se développer en rhizome - Fortin, André; Louesdon, Franck (2021)
Participer au renforcement de communautés de pratique autour de la cocréation et se faire inspirer pour se lancer dans l’aventure. Telle est l’intention de ce manuel complet et très illustré. Le Guide pratique sur la cocréation est issu des années d’expérience des auteurs sur le terrain. Il présente un processus de cocréation et fournit plusieurs éléments de réflexion à intégrer ainsi que des pistes concrètes menant à l’action.
Keywords: Co-création; Planification

Knowledge co-creation in the 21st century: A cross-country experience-based policy report - Kreiling, Laura; Paunov, Caroline (OECD Science, Technology and Industry Policy Papers, 2021)
The importance of knowledge co-creation – the joint production of innovation between industry, research and possibly other stakeholders, such as civil society – has been increasingly acknowledged. This paper builds on 13 cross-country case studies and co-creation experiences during the COVID-19 pandemic to characterise the diversity of knowledge co-creation initiatives and identify lessons for policy. The paper identifies a strong rationale for policy to support knowledge co-creation because the benefits of successful co-creation initiatives outweigh the initial co-ordination costs. Moreover, knowledge co-creation initiatives can contribute to democratising innovation. Successful initiatives engage all stakeholders and have effective governance and management structures. They also have clearly defined ownership and use rights of the collaborations’ outcomes and benefit from favourable conditions to operate, including temporary staff mobility and institutional set-ups that facilitate collaboration and effective communication among participants.
Keywords: COVID-19; Co-création; Innovation collaborative; OCDE; Politiques; Réservé UdeM; Science industrielle

Co-Creation for Social Innovation in the Ecosystem Context: The Role of Higher Educational Institutions - Kumari, Richa; Kwon, Ki-Seok; Lee, Byeong-Hee; Choi, Kiseok (Sustainability, 2020)
This study examined the role of Higher Educational Institutions (HEIs) in promoting, creating, and sustaining social innovation. Recently, HEIs have extended their contribution beyond the traditional function of teaching and research to perform in socio-economic problem-solving. Considering the increasing trends of higher education involvement in social innovation practices, this study tries to examine the tools such as learning processes and systemic thinking approach that could be helpful to align the function and responsibilities of HEIs towards social innovation. The objective is to develop a theoretical understanding of the "co-creation for social innovation" concept and to understand the functions and activities of HEIs that can contribute to this process. To promote co-creation for social innovation, HEIs should actively encourage collaborative learning tools that focus on open platforms for collective action and systemic change that help them to engage with society and strengthen their collaboration with social actors. Different activities such as mutual learning and knowledge diffusion using a transdisciplinary approach, technology-based learning and collaboration, and relational transformation are key enablers that can promote social innovation.
Keywords: Changement systémique; Co-création; Compétences; Formation; Laboratoires d'innovation; Libre accès; Rôle des universités

Sustainability-Oriented Social Innovation Design: The Value of Co-Creation - Yan, Wu; Lei, Ren; Keye, Li (2019 IEEE Eurasia Conference on Biomedical Engineering, Healthcare and Sustainability (ECBIOS), 2019)
From the perspective of sustainability, this paper analyzes how stakeholders realize sustainable social innovation through co-creation. Through literature and case analysis, based on the group classification of social networks, this paper proposes three elements of social innovation: place creation, situation creation and relationship structure, and further sorts out the co-creation of meaning co-creation, behavior co-creation and value co-creation. The research shows that co-creation is a practical activity based on cultural identity, group interaction and resource integration, and stakeholders can achieve the goal of sustainable social innovation through meaning co-creation, behavior co-creation and value co-creation.
Keywords: Co-création; Communautaire; Coopération; Durabilité; Développement durable; Idéation, dialogue et maillage; Innovation sociale; Innovation sociale durable; Nouvelles technologies; Recherche; Réservé UdeM